A systematic review of sound-based intervention programs to improve participation in education for children with sensory processing and integration challenges. Issue 2 (3rd April 2018) - Villasenor, Romana F.; Smith, Sarah L.; Jewell, Vanessa D.
ABSTRACT: This systematic review evaluates current evidence for using sound-based interventions (SBIs) to improve educational participation for children with challenges in sensory processing and integration. Databases searched included CINAHL, MEDLINE Complete, PsychINFO, ERIC, Web of Science, and Cochrane. No studies explicitly measured participation-level outcomes in education. Ten studies provided limited evidence supporting the use of SBIs based on preliminary positive effects on occupations, client factors, and performance skills related to participation in education. Stronger experimental designs are needed measuring educational participation. Therapists should use caution using SBIs for this population and outcome until further research clearly substantiates or refutes this intervention.